The Influence of Organizational Culture on Leadership Styles among Employees in Universiti Malaysia Perlis - Norzaililah, Zainoddin (2010)
This research studied the influence of organizational culture on leadership styles among administrative staffs in Universiti Malaysia Perlis (UNIMAP). This study measured three dimensions of organizational culture's characteristics (innovation and risk taking, team orientation and aggressiveness) as independent variables and three dimensions of leadership styles(transformational, transactional and situational) as dependent variables. By using stratified random sampling, a total of 129 sets of questionnaires were collected among the administrative staffs of grade 41 to 54 in UNIMAP. The data was subsequently analysed using SPSS linear regression analysis to test the influence of organizational culture. Overall, the study found that there is a positive significant between aggressiveness towards the three dimensions of leadership styles. However, organizational culture was also found to not having influence to the demographic factors in terms of age, gender, tenure and grade in most of the dimensions. In conclusion, these findings can be used to improve the governance system of UNIMAP as a new public university based on the recommendations stated.